The Effect of Light on Plastid Differentiation, Chlorophyll Biosynthesis, and Essential Oil Composition in Rosemary (Rosmarinus officinalis) Leaves and Cotyledons - Böszörményi, Andrea; Dobi, Adrienn; Skribanek, Anna; Pávai, Melinda; Solymosi, Katalin (Frontiers in Plant Science, 2020)
It is unclear whether light affects the structure and activity of exogenous secretory tissues like glandular hairs. Therefore, transmission electron microscopy was used to study plastid differentiation in glandular hairs and leaves of light-grown rosemary (Rosmarinus officinalis ’Arp’) plants kept for 2 weeks under ambient light conditions or in complete darkness. The basal cells of both capitate and peltate glandular hairs of light-grown leaves contained chloroplasts, while leucoplasts were observed in the other cells of both hair types, with tubuloreticular membrane structures resembling prolamellar bodies appearing only in stalk cell plastids of peltate glandular hairs. From the originally light-grown shoot tips of so-called dark-forced adult plants occasionally (typically at the end of summer or winter) new shoots with elongated internodes and pale leaves developed in the dark. Absorption and fluorescence spectroscopic analyses of the chlorophyllous pigment contents, the native arrangement of the pigment-protein complexes and photosynthetic activity confirmed that the first and second pairs of leaf primordia of dark-forced shoots were partially etiolated: in addition to low amounts of photoactive and non-photoactive protochlorophyllide pigment complexes they contained low amounts of residual chlorophylls, had etio-chloroplasts with prolamellar bodies and low grana and impaired photosynthesis. Darkness did not influence plastid structure in fifth leaves or secretory tissues with the exception of head cells of peltate glandular hairs in which rarely tubuloreticular membranes were observed. The cotyledons of 2-week-old dark-germinated rosemary seedlings accumulated high amounts of photoactive protochlorophyllide pigments and contained no chlorophylls, their etioplasts had highly regular prolamellar bodies similar to mesophyll etio-chloroplasts of leaves and clearly different from tubuloreticular membranes of secretory cells. Analyses of the essential oil composition obtained after solid phase microextraction and gas chromatography-mass spectroscopy showed that in addition to light, the age of the studied organ (i.e. first leaf primordia and leaf tip vs. fifth, fully developed green leaves) and the type of the organ (cotyledon vs. leaves) also strongly influenced the essential oil composition. Our data outline that light and developmental stage are both important factors to be considered in case of potential therapeutic, culinary or aromatic uses of rosemary leaves and their essential oils.